Initial modelled outputs at field scale - Gosme, M. (2016)
This report comprises Deliverable 6.16 in the project, which contributes to the third objective as it presents field-scale evaluation of innovations, in order to adapt and evaluate agroforestry designs and practices for locations where agroforestry is currently not-widely practised or declining. The modelling of outputs at field scale to support best agroforestry practices is an ongoing activity during the AGFORWARD project. This report highlights some of the outputs which has been produced in the form of three papers (either submitted or about to be submitted to a peer-reviewed journal) or in four presentations at the Third European Agroforestry Conference in May 2016